Assessing the school food environment and its role on healthy eating behaviours among school age children in Dar es Salaam, Tanzania. - Nyabasi Makori; Dyness Kejo; Hoyce Mshida; Beatrice Bachwenkizi; Devotha Mushumbusi; Zahara Daudi; Monica Chipungahelo; Ai Zhao; Anselm P Moshi (PLoS ONE)
School food environment plays a crucial role in shaping children's dietary habits and promoting healthy eating practices. The study investigated the school food environment in Temeke Municipality, Dar es Salaam, focusing on its role in promoting healthy eating among school-age children. A cross-sectional survey was conducted across four schools, with food vendors (N = 20) and teachers (N = 8) interviewed using structured questionnaires. The study aimed to assess food offerings, school oversight, and vendors' knowledge of food quality. The findings disclosed that 62.5% of the schools partially implemented school feeding guidelines, while 37.5% did not implement them. Among the surveyed schools, 37.5% had food storage facilities, 25.0% had functioning kitchens, and none had dining halls. The food environment included both healthy and unhealthy options, with 55.6% of food and beverages classified as healthy and 44.4% as unhealthy. Popular unhealthy items included samosas (95.5%), fried potato chips (87.0%), and fried mashed potato balls (73.9%). The study also compared the calorie portions of foods purchased by students with the Recommended Dietary Allowances (RDA) for different age groups. The percentage of RDA covered by these portions ranged from 8.0-19.0% for ages 5-8, 6.0-19.0% for ages 9-13, and 5.0-16.0% for ages 14-18. Furthermore, food vendors demonstrated low knowledge of food safety, hygiene, and nutrition, with only 22.0% aware of the national food guidelines. The overall food environment exposed students to unhealthy food options, with significant gaps in the implementation of health guidelines. Findings highlight the need for interventions to improve food offerings and promote healthier food choices around schools.